Legislative Intervention in Executive Social Programs: A Case Study of DPR Influence in the Distribution of the Program Indonesia Pintar (PIP) - Suksmoputri, Marva Sadira (Jurnal Indonesia Sosial Sains, 2026)
Study examines the dynamics of executive–legislative relations in Indonesia by analyzing the informal interventions of members of the House of Representatives (DPR) in the distribution of the Program Indonesia Pintar (PIP), a social assistance scheme formally administered by the executive. Although the legal framework assigns program implementation to the Ministry of Education, the Ministry of Religious Affairs, and local education offices, field practices show that legislators frequently position themselves as intermediaries or even gatekeepers in the allocation of PIP benefits. Drawing on policy documents, secondary data, and reported cases, this study argues that such legislative involvement constitutes an encroachment on executive functions, blurring institutional boundaries and weakening bureaucratic accountability, which directly impacts program integrity and governance. The paper situates these practices within theories of delegation, patronage politics, and informal institutions, demonstrating how political actors leverage social programs for constituency service and electoral advantage. Ultimately, the study highlights how the interaction between formal rules and informal political behavior affects the integrity, equity, and transparency of welfare program delivery in Indonesia.